Optical-force-induced bistability in nanomachined ring resonator systems - Bourouina, Tarik (2013)
This paper reports optical-force-induced bistability in a nanomachined ring resonator system. It consists of two ring resonators and a bus waveguide, whereby each ring resonator has a free-hanging arc that is perpendicularly deformable by an optical force and changes the effective refractive index of the system. Therefore, an optical bistability is induced into the nanomachined ring resonator system, in which the bistability band can reach 0.3 nm and 0.68 nm in the ring resonators 1 and 2, respectively. It has potential applications in optical signal processing area, such as all-optical switching and opto-mechanical memory.